2021
DOI: 10.1177/15248399211013002
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine Messaging on TikTok: Social Media Content Analysis

Abstract: Background The human papillomavirus (HPV) vaccine is viewed as a critical tool to protect against six HPV-related cancers. Vaccination is recommended from early adolescence through age 26 years. As young people have become increasingly involved in personal health-related decisions, there is a need to tailor HPV vaccine messaging and reach this priority population on social media and digital outlets. TikTok is a growing social media platform with approximately 70% of its users between the ages of 13 and 24 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Existing literature was consulted to identify specific types of evidence and persuasive arguments or strategies that are common in online public discourse about vaccination. Common types of evidence included: narratives; statistics; simple arguments; and scientific evidence [17,[26][27][28][29][30][31][32][33]. Initial team review of the dataset also resulted in the addition of codes to describe different types of evidence, such as lawsuits/legal arguments and hyperlinks to other sources.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature was consulted to identify specific types of evidence and persuasive arguments or strategies that are common in online public discourse about vaccination. Common types of evidence included: narratives; statistics; simple arguments; and scientific evidence [17,[26][27][28][29][30][31][32][33]. Initial team review of the dataset also resulted in the addition of codes to describe different types of evidence, such as lawsuits/legal arguments and hyperlinks to other sources.…”
Section: Discussionmentioning
confidence: 99%
“…In a TikTok study of both professional and non-professional videos that varied in pro/anti vaccine stance, it was determined that cancer and prevention messaging on HPV was more prevalent among pro-vaccine videos ( 39 ). Our findings are in concert with these in that all videos included in our sample were created by professionals and were pro-vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Many manuscripts in the published literature document that HPV content is prevalent on social media. Research has identified specific platforms such as Instagram ( 32 – 34 ), YouTube ( 35 37 ), Twitter ( 38 ), and Facebook ( 12 ) but we were only able to identify a single paper that examined HPV vaccine content on TikTok but was not limited to professionals ( 39 ). Examination of professional videos can help guide future health promotion efforts as this population begins to deliver more information on social media.…”
Section: Introductionmentioning
confidence: 99%
“…El análisis incluyó 150 publicaciones de cada partido, obtenidas aleatoriamente mediante la función "=RAND()" de Microsoft Excel (Microsoft Corp.) para todas las publicaciones de los perfiles de Instagram de los partidos. El número de unidades de análisis es análogo al de las investigaciones actuales sobre análisis de contenido de plataformas de redes sociales (Li et al, 2021;Boatman et al, 2021;Unni & Weinstein, 2021). Además de conocer la tasa de participación de cada partido, se obtuvieron datos sobre el número de seguidores de la cuenta oficial del partido, el número de me gusta de cada publicación con contenido visual relacionado con la investigación y el número de comentarios.…”
Section: Metodologíaunclassified